(untitled) (Global Journal of Management and Business Research, 2015)
Consumers began using more online sources today, thanks to the rapid development of technology and communication channels. The most important of these tools are social media. Consumers access to the information they need about goods and services which will be awarded through social media dramatically. It is clear that now day, social media components are popular like Facebook and Twitter have got an attention to consumer markets. Therefore, this study is aimed to determine the effect of social media in our lives in recent years and to determine the effects of social networks on the purchasing behavior of consumers in Pakistan. This study consisted of a sample of 1,000 young consumers between the age group of 18-50 years using social media platforms having an account in any of the social networks. Questionnaire was used to get the data of the study. The results form collected data indicate that the social media has a significant impact on consumption behavior in Pakistan.